Gastronomic Motivation and Place Attachment through the Mediating Role of Gastronomic Experience: Evidence from Bandung, Indonesia - Beni Ismarizal; Debi Rusmiati; Muhammad Mas Multazam; Ghifary Ramadhan (Centre of Excellence in Tourism Udayana University, 2025)
Gastronomy plays a central role in shaping tourists’ travel decisions, as authentic culinary experiences connect visitors with local culture and strengthen their attachment to destinations. This study examined the effect of gastronomic motivations on place attachment, with gastronomic experience as a mediating variable. A quantitative approach using Structural Equation Modeling (SEM) with AMOS 24 was employed to rigorously test the proposed relationships. Data were obtained from 400 valid questionnaires completed by tourists who had visited Bandung and tasted local cuisine within the past year. The sample size was determined using the Lemeshow formula, as the population size was unknown. The analysis involved confirmatory factor analysis (CFA) to assess construct validity and measurement reliability, followed by structural model testing. The results demonstrated that gastronomic motivations had a significant positive effect on both gastronomic experience and place attachment. Furthermore, gastronomic experience was found to significantly enhance place attachment, confirming its mediating role. These findings highlight the importance of gastronomy as both a motivational and experiential driver of tourists’ emotional bonds with destinations. From a managerial perspective, the study provides practical and strategic insights for destination managers and tourism stakeholders in developing marketing strategies and innovative tourism products that emphasize local culinary identity and community-based gastronomic experiences. Limitations include the single-destination focus, cross-sectional and self-reported data, and limited generalizability. Future research should adopt longitudinal designs or comparative studies across multiple destinations.